Molecular genetic characteristics of elite rugby union athletes - Heffernan, S. M. (Manchester Metropolitan University, 2016)
The capacity to achieve elite athletic success is known to be highly heritable and physiologically complex. Recently, there has been a substantial rise in the number of peer reviewed sports genomics publications, however the majority of these have focused on the genetic components of either strength/sprint/power or endurance athletes, with little attention given to team sports. Since rugby union (RU) athletes perform under a well-defined set of rules and parameters, which are ubiquitous across all playing positions, they present an ideal cohort via which to study the importance of genetic variation in sport and as such is the purpose of the present thesis. The aims of the present thesis were, firstly, to recruit a large cohort of elite RU athletes and compare the genetic profile of these athletes to that of a control population. Secondly, because of the large physiological differences between elite RU playing position, the present thesis further aimed to compare the genetic diversity in RU inter-positional variation. 1164 participants, consisting of 454 elite RU athletes and 710 controls from the general population were recruited for the present thesis. Genotyping data was generated for SNPs within the APOE e4 (rs429358 and rs7412), ACTN3 (rs1815739), ACE I/D or ACE tag SNP (rs4341), COL5A1 (rs12722 and rs3196378) and FTO (rs9939609) genes. Only the COL5A1 SNPs were different when comparing the entire elite RU cohort to controls. However, observations of APOE e4 frequency did reveal that ~30% of elite RU athletes are at higher risk of poor outcome following mTBI (concussion). Regarding playing position, both ACTN3 and FTO showed position specific variation, with the greatest associations in the backs playing position. There were no associations between elite RU athletes and controls for ACE I/D. When incorporating all of the above SNPs into a polygenic profile, the entire elite RU cohort, the backs and forwards showed significant deviation from controls. Interestingly by using an ROC model the present thesis identified significant polygenic sensitivity in discriminating between elite RU backs and forwards which trended towards the backs. The data generated in the present thesis are the first to show genetic variation in a large cohort of elite RU athletes, with particular emphasis on positional specificity. These data are only the `tip of the iceberg` in understanding the molecular aspect of elite RU physiological underpinnings and analysis of many more variants are required in addition to replication of the present results. Nonetheless, these data are the first step in this understanding and may have implications in positional selection, position specific training and injury management, in the future. Follow up studies should focus on further recruitment of elite RU athletes and combining genetic data with phenotypic data, specific to elite RU athletes and with particular attention to injury susceptibility. Restricted to Repository staff only until 14 February 2020